Championing inclusive terminology in ecology and evolution. (May 2023) - Cheng, Susan J.; Gaynor, Kaitlyn M.; Moore, Alex C.; Darragh, Kathy; Estien, Cesar O.; Hammond, J.W.; Lawrence, Christopher; Mills, Kirby L.; Baiz, Marcella D.; Ignace, Danielle; Khadempour, Lily; McCary, Matthew A.; et al.
Abstract: Amid a growing disciplinary commitment to inclusion in ecology and evolutionary biology (EEB), it is critical to consider how the use of scientific language can harm members of our research community. Here, we outline a path for identifying and revising harmful terminology to foster inclusion in EEB.